Drag augmentation systems for space debris mitigation. (November 2021) - Serfontein, Zaria; Kingston, Jennifer; Hobbs, Stephen; Holbrough, Ian E.; Beck, James C.
Abstract: Space debris is a critical threat to future and on-going missions. The commercialisation of the space sector has led to a rapid growth in the number of small satellites in recent years, which are adding to the already high number of objects currently in low-Earth orbit (LEO). Low-cost small satellites operators are under increasing pressure to comply with debris mitigation guidelines as part of the application process for a launch licence. Drag augmentation systems are a potential low-cost and low-impact solution for small satellites. By increasing the effective area of a satellite, and therefore its drag, these sails reduce the de-orbit period of a satellite, subsequently reducing the probability of significant collisions and supporting the sustainable use of space. Cranfield University are developing a family of drag augmentation systems (DAS) to assist in the long-term conservation of the space environment. The DAS are lightweight, cost-effective, reliable sails deployed at end of mission. Currently three of the drag sails designed, manufactured, and tested at Cranfield University are in orbit and two of the devices have successfully deployed their sails. This paper will discuss these sails and will highlight results from recent studies; examining the scalability of the system, the vehicle dynamics after sail deployment, the medium-term impact of the sail on the host satellite's ability to continue operations, and the long-term effect of the sail on the demisability of the satellite. The DAS technology has a strong enabling potential for future space activities, allowing satellites to operate responsibly and sustainably. Highlights: Drag augmentation systems for end-of-life de-orbit of satellites. Low-cost, simple solutions for future space debris mitigation. Assessment of drag sail scalability, deployment dynamics and demisability. Impact of drag sail on host satellite; short- and long-term vehicle dynamics. Potential mission extension; de-risking de-orbit device.